Human milk peptides differentiate between the preterm and term infant and across varying lactational stages. Issue 10 (29th September 2017) - Dingess, Kelly A.; de Waard, Marita; Boeren, Sjef; Vervoort, Jacques; Lambers, Tim T.; van Goudoever, Johannes B.; Hettinga, Kasper
Abstract : Variations in endogenous peptide profiles, functionality, and the enzymes responsible for the formation of these peptides in human milk are understudied. Abstract : Variations in endogenous peptide profiles, functionality, and the enzymes responsible for the formation of these peptides in human milk are understudied. Additionally, there is a lack of knowledge regarding peptides in donor human milk, which is used to feed preterm infants when mother's own milk is not (sufficiently) available. To assess this, 29 human milk samples from the Dutch Human Milk Bank were analyzed as three groups, preterm late lactation stage (LS) ( n = 12), term early ( n = 8) and term late LS ( n = 9). Gestational age (GA) groups were defined as preterm (24–36 weeks) and term (≥37 weeks). LS was determined as days postpartum as early (16–36 days) or late (55–88 days). Peptides, analyzed by LC-MS/MS, and parent proteins (proteins from matched peptide sequences) were identified and quantified, after which peptide functionality and the enzymes responsible for protein cleavage were determined. A total of 16 different parent proteins were identified from human milk, with no differences by GA or LS. We identified 1104 endogenous peptides, of which, the majority were from the parent proteins β-casein, polymeric immunoglobulin receptor, αs1 -casein, osteopontin, and κ-casein. The absolute number of peptides differed by GA and LS with 30 and 41 differing sequences respectively ( p < 0.05) Odds likelihood tests determined that 32 peptides had a predicted bioactive functionality, with no significant differences between groups. Enzyme prediction analysis showed that plasmin/trypsin enzymes most likely cleaved the identified human milk peptides. These results explain some of the variation in endogenous peptides in human milk, leading to future targets that may be studied for functionality.